Secondary education influences on higher education performance - Sommerville, Ted (South African Journal of Higher Education, 2016)
This mixed methods study followed a cohort of students through an undergraduate medical programme. It investigated demographic variables (sex, age, race, language, finance, education level, high school, and matric score) as influences on students’ assessment marks. Marks were analysed by means of the general linear method (GLM) for within-group differences, and by a generalised estimating equation (GEE) for overall significance. Most variables showed significantly different subgroups on GLM analysis. However, only high school quintile, previous higher education, the assessments them¬selves and matric points showed overall significance on GEE analysis. Semi-structured student and staff interviews explored the surprising influence of students’ high schools on their assessment marks. The differences seen between students from schools in different quintiles may be attributable to the schools’ financial resources. However, I argue that Coleman’s and Bernstein’s observations of class differences are apposite, and that school quintile stands here as a surrogate for socio-economic class.